Methodical instructions for performing the laboratory work "Configuration of parts" - Butova, O. A.; Samynina, M. G.; Domochka, Lidiia Vladyslavivna (My University, 2023)
Methodical instructions for the laboratory work on the discipline «Fundamentals of Electronic Device Design » for students of all forms of education in the specialty 171 «Electronics» on the discipline «Fundamentals of Electronic Device Design», which is learned by the students of the «Industrial and Biomedical Electronics» department. SOLIDWORKS is a computer-aided design (CAD) system that allows you to create electronic models of parts and assembly units with the ability to generate working drawings based on them. In the process of preparing for the class, the student has to study questions about the features of using the SOLIDWORKS automated design system and master the skills of creating models in the program. In the course of performing this laboratory work, students work out the possibilities of creating configurations of parts in various ways and have to: − know the sequence of actions when building part models and the main methods of creating their configurations; − be able to apply the acquired theoretical knowledge when creating details, as well as configurations of these details. Methodological instructions include: − the purpose of work; − a step-by-step description of the sequence of work performance on an example; − tasks for the laboratory work; − control questions. Methodological instructions provide methods for creating configurations of parts and consider an example of step-by-step configuration creation in several ways, which will help in effective and practical mastering the material on the discipline «Fundamentals of Electronic Device Design». Performance and protection of laboratory work is carried out individually.
Keywords: methodical instructions; information technology; methodology for creating a table of parameters; adding Excel spreadsheets; computer-aided design; software tools